Comparative Effectiveness of Virgin Coconut Oil and Olive Oil on Striae Gravidarum in Pregnant Women during theSecond and Third Trimesters at TPMB Sumartini Purwakarta, 2026 - Elma Yulia; Dita Humaeroh; Maulida Lathifah (Public Health Journal, 2026)
Striae gravidarum is a skin condition experienced by the majority of pregnant women, with a global prevalence of 50–70% (WHO, 2024), 70–95% in Indonesia (2025), and a preliminary survey at TPMB Sumartini Purwakarta (2026) identifying approximately 40 cases. This condition affects mothers physically, psychologically, functionally, and in terms of quality of life. Virgin Coconut Oil (VCO), rich in lauric acid, and olive oil, containing oleic acid and antioxidants, are believed to help maintain skin elasticity. This study used a quasi-experimental two-group pretest–posttest design with 36 respondents (18 receiving VCO, 18 receiving olive oil). The severity of striae was measured using the Davey Score, and the data were analyzed using the Paired Samples T-Test and Independent Samples T-Test. The results showed a significant decrease in scores in both groups (p = 0.000). The mean score reduction in the VCO group was 2.00, while in the olive oil group it was 1.33. The Independent Samples T-Test showed a significant difference (p < 0.05), with VCO proving more effective. VCO was shown to be more effective than olive oil in reducing the severity of striae gravidarum; therefore, its routine use from the second trimester onward is recommended as a preventive measure to maintain skin elasticity, minimize the risk of striae, and improve the comfort and confidence of pregnant women.